(untitled) (Az-Zaida: Jurnal Ilmu Multidisiplin, 2026)
Arabic language learning in Indonesia still faces various challenges, particularly related to students’ low learning motivation and the limited variation of teaching strategies. The development of digital media, especially YouTube, offers new opportunities for Arabic language instruction. This study examines Arabic teaching strategies applied on the Neng Repi YouTube channel, focusing on instructional delivery and its relevance to Arabic language learning. The research question addresses how Arabic teaching strategies are implemented in the learning videos uploaded on the Neng Repi YouTube channel. This study employed a qualitative approach using descriptive research design. Data were collected through observation of Arabic learning videos on the channel and relevant documentation. Data analysis was conducted using descriptive qualitative techniques, including data reduction, data display, and conclusion drawing. The findings reveal that the teaching strategies include gradual material presentation, repetition in pronunciation, effective use of audio-visual media, contextual examples, and a communicative teaching style. These strategies contribute to more effective and engaging Arabic language learning and align with the characteristics of learners in the digital era. The study highlights the potential of YouTube as an alternative medium for Arabic language teaching.